PENGARUH MODEL PEMBELAJARAN THINK PAIR SQUARE BERBANTUAN LKPD BERBASIS DISCOVERY LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII - Nabiilah, Aisyah (Departemen Matematika, 2023)
Students must possess mathematical communication abilities as one of their mathematical competencies. In actuality, however, this aptitude in the eighth grade of SMPN 25 Padang remains relatively modest. The use of learning models that discourage active participation in communicating mathematical concepts is one of the contributing factors. The Think Pair Square cooperative learning model and Discovery Learning-based LKPD will be utilized to address these issues. This research is quasi-experimental and descriptive in nature, with a design consisting solely of randomized control groups. The hypothesis test's P-value of 0.035 indicates that H0 should be rejected based on the research findings. Thus, the conclusion reached is that the mathematical communication skills of eighth-grade SMPN 25 Padang students whose learning uses the Think Pair Square model supported by discovery learning-based LKPD are superior to those of students whose learning uses conventional models.Keywords. – Cooperative Learning, Think Pair Square, Discovery Learning, Mathematical Communication Abilities